The Relevance of Microbial Fermentation for Long-Term Health Effects of High Protein Diets - Rajilić-Stojanović, Mirjana (Archives of Pharmacy, 2024)
Proteins are important macronutrients with several beneficial health effects. Today, protein-rich diets are gaining popularity, especially in the context of achieving or preserving a healthy weight. However, epidemiological studies associate long-term consumption of protein-rich diets with adverse health outcomes and increased mortality. These adverse effects, at least partially, are mediated by the activity of microbial products obtained by protein fermentation. Undigested food components reach the colon, where the gut microbiota transforms food residues into various metabolites. Given that side chain groups of amino acids are chemically heterogeneous, undigested proteins provide a mix of substrates for microbial fermentation. By using different amino acids, the gut microbiota can produce toxic, genotoxic, and carcinogenic compounds, but also metabolites that impair normal insulin signaling and cardiovascular function. Biological activity of microbial metabolites can contribute to the development of cardiovascular diseases and cancer, which are associated with high-protein diets. In principle, microbiota metabolic products are beneficial for humans and complementary to human metabolism. However, when diet composition is out of balance (e.g. when proteins are present in an excessive amount), microbiota activity shifts towards production of hazardous metabolites. Therefore, the gut microbiota and its activity must be taken into consideration when designing nutritional strategies to promote health.
Keywords: gut microbiota; high-protein diets; cancer; cardiometabolic risk; fermentation